Debt, equity and the equity price puzzle - Daria Finocchiaro; Caterina Mendicino (Sveriges Riksbank, 2015)
We show that in a model with equity and debt financing, the specfication of the borrowing constraint is crucial to generate empirically plausible responses of macro variables and asset prices to financial shocks. The interaction between financial frictions and labor demand, as in Jermann and Quadrini (2012), is key to the result. A collateral constraint a la Kiyotaki and Moore (1997) augmented with a working capital assumption generates similar results on impact.
Keywords: E32; E44; 330; liquidity shocks; collateral constraints; stock prices; co-movement